PREPARATION OF THE ENZYME SOLUTION FROM THE WHOLE BOVINE ABOMASUM FOR MODIFICATION OF PROPERTIES OF THE COLLAGEN CONTAINING RUMEN - B. A. Bazhenovа; A. М. Danilov (Теория и практика переработки мяса)
At present, a significant experience in the effective processing of secondary raw material resources of the meat industry has been accumulated. However, a proportion of their use for food purposes remains to be low. First of all, this concerns processing of the multi-chambered stomach of farm animals. A prospective direction of scientific research is the complex use both of food and biotechnological potential of these by-products. In this work, a possibility of the enzymatic modification of the collagen-containing bovine rumen with the pepsin solution (lysate) was studied. The pepsin solution was obtained by the autolysis method from the enzyme containing chamber of the cattle stomach — the whole abomasum; whereas, usually the lysate is obtained from the abomasal mucosa, which separation is quite a labor consuming process. The investigations established that the lysate prepared on the basis of the whole bovine abomasa had the proteolytic activity along with the collagenase one. To increase the effectiveness of pepsinogen extraction, the tough connective tissue of abomasa was minced and loosened with the acidic solution of polyphosphate, which also has the bacteriostatic activity. Based on the results of the experiment, the rational technology of pepsin extraction from the whole abomasa without preliminary separation of the mucosa was developed. In addition, a possibility of the enzymatic modification of the collagen containing bovine rumen using the obtained lysate with improvement of the functional and technological characteristics was proved. The regimes and parameters of the process of the enzymatic modification of the rumen tissue properties were experimentally established.